IMPLEMENTATION OF AHP-TOPSIS AS A SUPPORT FOR MAKING DECISIONS ON MICRO BUSINESS FUNDING IN SAMBAS REGENCY - Noerul Hanin; Della Zaria; David Jordy Dhandio; Dadan Kusnandar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The economy is one of the fields affected by the Covid-19 pandemic in the world, including Indonesia. One of the drivers of the economy in Indonesia is Micro, Small and Medium Enterprises (MSMEs). Among the three types of businesses, micro-enterprises contribute the most to Indonesia's Gross Domestic Product. Therefore, an analysis of the decision support system for financing micro-enterprises in Indonesia is carried out. This study aims to determine the application of decision support methods in selecting micro-enterprises that are entitled to receive grants and appreciation for developing their business. The choice of Sambas Regency as the case study location was due to the good development of micro-enterprises and one of the front lines in exporting products to other countries. The method used is a collaboration between the Analytical Hierarchy Process (AHP) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Through the process of weighing the criteria with AHP and several stages with TOPSIS, the results are obtained in the form of preference values and sequences of micro businesses that are eligible to receive funds. For the category of grants, it was found that the most feasible business to be financed was Roemah Jamoer Ikram, while for the category of appreciation funds, the most feasible business to be financed was Amplang 9. Thus, the analysis of supporting micro business financing using the AHP-TOPSIS method was successfully carried out with the output in the form of micro business rating results.